Do corporate managers skimp on shareholders' dividends to protect their own retirement funds? - Eisdorfer, Assaf; Giaccotto, Carmelo; White, Reilly (Journal of Corporate Finance, 2015)
What is the impact of long-term executive compensation, particularly large pension payouts, on the firm's current dividend policy? We argue that managers with high pension holdings are less likely to adopt a high dividend policy that can risk their future pension payouts. Using a hand-collected actuarial pension dataset we show that (i) dividend payments are significantly lower when manager compensation relies more heavily on pension payouts; (ii) higher compensation leverage and inside debt have a significant negative effect on dividend payments net of stock repurchases; and (iii) the negative effect of pension on dividend is significantly weaker when pensions are protected in a pre-funding rabbi trust. We show further that this agency behavior reduces firm performance.